Misja w firmie społecznie odpowiedzialnej - Witek-Crabb, Anna (Mission Statement in Socially Responsible Companies, 2008)
The aim of this paper is to determine the characteristics of a mission statement in a socially responsible company. It seems that in order to create an effective mission statement in a CSR company, it is necessary to care for a few elements: mission integrity with the company's activities and organizational culture, inclusion of the values coherent with the CSR concept, and focus on the stakeholder needs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 415-424